Differential patterns of nitrogen and δ15N in soil and foliar along two urbanized rivers in a subtropical coastal city of southern China. (January 2019) - Mgelwa, Abubakari Said; Hu, Ya-Lin; Liu, Jin-Fu; Qiu, Qingyan; Liu, Zheng; Yannick Ngaba, Mbezele Junior
Abstract: Urbanization usually pollutes the environment leading to alterations in key biogeochemical cycles. Therefore, understanding its effects on forest nitrogen (N) saturation is becoming increasingly important for addressing N pollution challenges in urban ecosystems. In this study, we compared soil (N availability, net N mineralization, net nitrification, and δ 15 N) and foliar (N concentrations and δ 15 N) variables in upstream, midstream and downstream forest stands of Bailongjiang River (BJR; more urbanized) and Wulongjiang River (WJR; less urbanized), the two branches of the Minjiang River Estuary. Total soil N, ammonium, nitrate, net N mineralization and nitrification rates, as well as soil δ 15 N were significantly higher in BJR compared with WJR forest stands. While no substantial difference in foliar N concentrations was noted between rivers, foliar δ 15 N was on average more than 2.5 times higher in BJR than WJR forest stands. Across the study area, foliar δ 15 N was positively related to soil δ 15 N, which also had positive linear relationships with soil nitrate concentrations, net N mineralization and net nitrification rates. Moreover, all variables except foliar δ 15 N and ammonium concentrations showed decreasing patterns in the order: upstream > midstream > downstream along the BJR forest stands. Soil ammonium and foliar values (N concentrations and δ 15 N) revealed clear patterns along the WJR, with the former increasing and the latter decreasing from the upstream to downstream forest stands. Our findings indicate an increase in urbanization-induced N inputs from the WJR to BJR and that forest stands along the BJR especially at the upstream have higher N availability and are shifting rapidly towards N saturation state. These results emphasize the need for effective N pollution control in urban environments through sustainable urban planning. Graphical abstract: Image Highlights: Bailongjiang (BJR) and Wulongjiang (WJR) rivers differ in urbanization levels. Soil N availability and N cycling rates were higher in BJR than WJR forest stands. Soil and foliar δ 15 N were more enriched in BJR compared with WJR forest stands. BJR forest stands are shifting rapidly towards N saturation state. Abstract : Our results indicate an increase in urbanization-induced N inputs from the WJR to BJR and that urban forests along the BJR are shifting rapidly towards N saturation state.